2018
DOI: 10.1002/dep2.46
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on the Luoquan Glaciation (Ediacaran‐Cambrian) of North China

Abstract: The Luoquan Formation provides a record of the Ediacaran-Cambrian glaciation in the North China Craton. The sedimentary record is well expressed in the Henan Province along the central China orogen, and includes a rich archive of striated pavements, diamictites, and dropstone-bearing laminites. A reappraisal of the sedimentological evolution of the Luoquan Formation notes the following features. First, striated pavements with crosscutting striations do not necessarily record multiple phases of glacial (re)adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Most are not very well constrained because of their age and/or that their glacigenic nature is currently under discussion (see compilations of Arnaud et al 2011;Youbi et al 2020). The two most likely ones are located on the North China craton (Le Heron et al 2018) and in Tasmania (Calver et al 2004). Another glacial deposit (Moelv diamictite) with a suggested Ediacaran age also crops out in Baltica (Bingen et al 2005), but at present available age data are not sufficient to constrain an age younger than the Gaskiers glaciation.…”
Section: Discussionmentioning
confidence: 99%
“…Most are not very well constrained because of their age and/or that their glacigenic nature is currently under discussion (see compilations of Arnaud et al 2011;Youbi et al 2020). The two most likely ones are located on the North China craton (Le Heron et al 2018) and in Tasmania (Calver et al 2004). Another glacial deposit (Moelv diamictite) with a suggested Ediacaran age also crops out in Baltica (Bingen et al 2005), but at present available age data are not sufficient to constrain an age younger than the Gaskiers glaciation.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon isotope excursion of the carbonates suggested the Dongpo Formation can be correlated with the Nanhua carbonates in South China (L. Zhang et al, 2008). However, recent studies reported the Asteridium-Heliosphaeridium-Comasphaeridium fossil assemblages, which first appeared in the Cambrian, both in the Luoquan and Dongpo formations (Le Heron et al, 2018;P. C. Wang, 2015;B.…”
Section: The Correlation Of the "Great Unconformity"mentioning
confidence: 99%
“…In addition, the Great Unconformity between the Precambrian basement and Cambrian sedimentary cover, particularly in Laurentia with extensive documentation, was closely related with the dramatic change of the surface and deep geodynamic process during the Proterozoic to the Phanerozoic (Allen & Campbell, 2008;Meert & Lieberman, 2008;Olierook et al, 2019;Squire, Campbell, Allen, & Wilson, 2006). In the North China Craton (NCC), this unconformity was represented by the depositional hiatus between the Precambrian metamorphic basement and the Cambrian successions in most regions (T. C. He et al, 2016;Le Heron, Vandyk, Wu, & Li, 2018;M. Li, Vandyk, et al, 2020;Tang, Pang, Yuan, Wan, & Xiao, 2015;B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Cambrian-Early Ordovician climate is generally considered as a greenhouse [17,18], plenty of evidence for climate oscillations and even the presence of glaciations in the Early Cambrian and Late Cambrian have been identified in recent decades [19]. This includes the presence of tillites and abundant dropstones, as well as specific sedimentary structures (ice-push lineations and structures implying frozen sediment) in the Early Cambrian [10,20,21], and evidence for freezing conditions even in the relatively low-latitudes in the Late Cambrian [22].…”
Section: Brief Review Of Early Paleozoic Climate and Glendonite Findingsmentioning
confidence: 99%